Stator core for an electrical power system

By using a polymer composition containing a thermogenic liquid crystal polymer as an insulating member in the stator core in the electric vehicle power system, the shortcomings of the existing materials in terms of heat resistance, high flowability and thermal conductivity are solved, and higher manufacturing simplicity and overall performance are achieved.

CN119923785APending Publication Date: 2025-05-02TICONA LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280100405.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-22
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The stator core materials in the existing electric vehicle power systems are difficult to achieve good heat resistance, high flowability and high thermal conductivity, resulting in insufficient manufacturing simplicity and overall performance.

Method used

A polymer composition containing a thermogenic liquid crystal polymer is used as an insulating member and is arranged in the intermediate groove of the stator core, showing low melt viscosity and high load deflection temperature, and having high thermal conductivity and electrical insulation.

Benefits of technology

The stator core is achieved with high flowability, good heat resistance and high thermal conductivity, improved manufacturing simplicity and overall performance, and enhanced the flexibility and impact resistance of the stator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923785A_ABST
    Figure CN119923785A_ABST
Patent Text Reader

Abstract

A stator core is provided, the stator core comprising: a stator body from which a plurality of spaced apart slot segments extend, with intermediate slots defined between the slot segments; and an insulating member disposed within the at least one intermediate groove. The insulating member includes a polymer composition including a polymer matrix including a thermotropic liquid crystal polymer. The polymer composition exhibits a melt viscosity of about 300 Pa-s or less and a load deflection temperature of about 170 DEG C or more.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] An electric vehicle, such as a battery electric vehicle, a plug-in hybrid electric vehicle, a mild hybrid electric vehicle, or a full hybrid electric vehicle, typically has an electric powertrain that includes an electric propulsion source (e.g., a battery) and a transmission. The electric motor used in such a vehicle typically includes a powertrain that includes a stator and a rotor disposed within a housing. The rotor can be attached to a generally cylindrical shaft that is rotatably mounted in the housing and coaxial with the stator. The stator can include a generally cylindrical stator core having a plurality of slots formed therein. A plurality of stator wires (windings) are formed in the slots of the stator core in a predetermined multi-phase (e.g., three-phase or six-phase) winding pattern. The slot segments are typically insulated from the core by a sheet insulator. A typical sheet insulator is Nomex®. TM Paper (often called "slot liner"). While somewhat beneficial, it is often difficult to incorporate this material into the small slots of the stator core. In addition, Nomex TM Paper is costly and lacks various beneficial properties, such as good heat resistance, high flowability, and high thermal conductivity, which can improve the ease of manufacturing and overall performance of the stator. Therefore, there is a need for an improved stator core for use in the powertrain of an electric vehicle. Summary of the invention

[0002] According to one embodiment of the present invention, a stator core is disclosed, comprising a stator body extending from a plurality of spaced slot segments, wherein intermediate slots are defined between the slot segments. An insulating member is disposed in at least one intermediate slot. The insulating member comprises a polymer composition comprising a polymer matrix comprising a thermotropic liquid crystal polymer. The polymer composition exhibits a melt viscosity of about 300 Pa-s or less and a load deflection temperature of about 170°C or more.

[0003] Other features and aspects of the present invention are described in more detail below. BRIEF DESCRIPTION OF THE DRAWINGS

[0004] A full and enabling disclosure of the invention including the best mode thereof occurring to one of ordinary skill in the art is more particularly set forth in the remainder of the specification including reference to the accompanying drawings in which:

[0005] Figure 1a and Figure 1b An embodiment of the stator core of the present invention is shown before contact with an insulating member;

[0006] Figure 2a , 2b and 2c show one embodiment of the stator core of the present invention after contact with an insulating member (e.g., overmolding);

[0007] Figure 3a, 3b and 3c shows the inclusion of Figure 2a and Figure 2b An embodiment of a stator comprising a combination of a stator core and a stator winding;

[0008] Figure 4 is an embodiment of a power system that can employ the stator of FIG. 3 ; and

[0009] Figure 5 One embodiment of an electric vehicle to which the stator core of the present invention can be applied is shown. DETAILED DESCRIPTION

[0010] Those skilled in the art will appreciate that the current discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.

[0011] Generally speaking, the present invention relates to a stator core for a power system of an electric vehicle. The stator core includes a stator body, which includes a plurality of spaced-apart and axially extending slot segments, and intermediate slots are defined between the slot segments. An insulating member is disposed within at least a portion of the slot. Notably, the insulating member comprises a polymer composition that includes a liquid crystal polymer and exhibits a combination of high fluidity and good heat resistance. More specifically, the composition may exhibit a melt viscosity of about 300 Pa-s or less, about 150 Pa-s or less in some embodiments, about 5 to about 100 Pa-s in some embodiments, about 10 to about 95 Pa-s in some embodiments, and about 15 to about 80 Pa-s in some embodiments, which is 1,000 s according to ISO 11443:2021. -1 The shear rate and the temperature (e.g., about 350°C) higher than the melting temperature of the composition are measured. The deflection temperature under load (DTUL) is a measure of short-term heat resistance, which may also remain relatively high. For example, the DTUL may be about 170°C or higher, about 200°C or higher in some embodiments, about 210°C to about 300°C in some embodiments, and about 220°C to about 280°C in some embodiments, for example, according to ISO 75:2013 under a load of 1.8MPa. Even at such a DTUL value, the ratio of the melting temperature to the DTUL value may remain relatively high. For example, the ratio may be in the range of about 0.5 to about 1.00, about 0.6 to about 0.95 in some embodiments, and about 0.65 to about 0.85 in some embodiments. The specific melting temperature of the polymer composition may be, for example, about 250°C to about 440°C, about 260°C to about 400°C in some embodiments, and about 300°C to about 380°C in some embodiments.

[0012] In addition to showing good flow properties and heat resistance, the polymer composition can also show high thermal conductivity. This high thermal conductivity value allows the composition to form a thermal path so that heat is transferred from the conductive elements of the stator. In this way, "hot spots" can be quickly eliminated, and the overall temperature can be reduced during use. For example, the polymer composition can show about 2W / mK or higher, about 2.5 to about 15W / mK in some embodiments, about 3 to about 10W / mK in some embodiments, and about 4 to about 8W / mK in-plane (or "flow") thermal conductivity in some embodiments, which is measured according to ASTM E 1461-13 (2022). Similarly, the polymer composition can show about 0.8W / mK or higher, about 1 to about 12W / mK in some embodiments, and about 2 to about 8W / mK in some embodiments. The cross-plane (or "cross flow") thermal conductivity, this is measured according to ASTM E 1461-13 (2022). The composition may also exhibit a through-plane thermal conductivity of about 0.2 W / mK or more, in some embodiments, about 0.3 W / mK or more, in some embodiments, from about 0.5 to about 4 W / mK, and in some embodiments, from about 0.6 to about 2 W / mK, as measured in accordance with ASTM E 1461-13 (2022).

[0013] Despite the thermal conductivity, the polymer composition can still have electrical insulation and can maintain a high short-term dielectric strength even when exposed to an electric field. "Dielectric strength" generally refers to the voltage that a material can withstand before breakdown occurs. For example, the polymer composition can generally exhibit a dielectric strength of about 10 kilovolts / millimeter (kV / mm) or higher, about 15kV / mm or higher in some embodiments, and about 25kV / mm to about 60kV / mm in some embodiments, for example, according to IEC 60234-1:2013. The insulating properties of the polymer composition can also be characterized by a high relative tracking index (CTI), for example, about 150 volts or higher, about 170 volts or higher in some embodiments, about 200 volts or higher in some embodiments, and about 220 to about 350 volts in some embodiments, for example, according to IEC60112:2003 at 3 mm thickness.

[0014] Despite the above characteristics, the polymer composition can still maintain high strength, thereby providing enhanced flexibility and impact resistance. For example, the polymer composition can exhibit a tensile stress at break (i.e., strength) of about 40 MPa to about 300 MPa, about 50 MPa to about 250 MPa in some embodiments, and about 70 to about 200 MPa in some embodiments; about 0.5% or more, about 1% to about 8% in some embodiments, and about 2% to about 5% tensile strain at break (i.e., elongation) in some embodiments; and / or about 5,000 to about 30,000 MPa, about 6,000 MPa to about 25,000 MPa in some embodiments, and about 9,000 MPa to about 22,000 MPa in some embodiments. Tensile properties can be determined according to ISO 527:2019 at a temperature of 23 ° C. The composition may also exhibit a flexural strength of about 20 MPa or greater, in some embodiments about 50 to about 300 MPa, in some embodiments about 70 to about 250 MPa, in some embodiments about 80 to about 200 MPa; and / or a flexural modulus of about 10,000 MPa or less, in some embodiments about 5,000 MPa to about 30,000 MPa, in some embodiments about 8,000 MPa to about 25,000 MPa, and in some embodiments about 9,000 MPa to about 20,000 MPa. Flexural properties may be measured at a temperature of 23° C. according to ISO 178:2019. The polymer composition may also exhibit high impact strength, which may provide enhanced flexibility to the resulting part. For example, the polymer composition may exhibit a flexural modulus of about 2 kJ / m 2 or greater, in some embodiments from about 4 to about 20 kJ / m 2 , and in some embodiments from about 6 to about 18 kJ / m 2 Unnotched Charpy impact strength of about 10 kJ / m 2 or greater, in some embodiments from about 15 to about 50 kJ / m 2 , and in some embodiments from about 20 to about 40 kJ / m 2 The notched charpy impact strength is measured according to ISO 179-1:2010 at a temperature of 23°C.

[0015] Various embodiments of the present invention will now be described in further detail.

[0016] I. Polymer composition

[0017] A. Polymer Matrix

[0018] As described above, the polymer matrix includes at least one liquid crystal polymer. For example, the liquid crystal polymer generally accounts for about 50 wt.% to 100 wt.%, in some embodiments, about 70 wt.% to 100 wt.%, and in some embodiments, about 90 wt.% to 100 wt.% (e.g., 100 wt.%) of the polymer matrix. Liquid crystal polymers are generally classified as "thermotropic" in that they can have a rod-like structure and exhibit crystallization behavior in their molten state (e.g., thermotropic nematic state). Such polymers generally have a DTUL value of about 200°C to about 340°C, in some embodiments, about 210°C to about 300°C, and in some embodiments, about 220°C to about 280°C, which is measured under a load of 1.8 MPa according to ISO 75-2:2013. The polymer also has a relatively high melting temperature, which is, for example, about 250°C to about 440°C, in some embodiments, about 260°C to about 400°C, and in some embodiments, about 300°C to about 380°C. The polymer may be formed from one or more types of repeating units known in the art. For example, a liquid crystal polymer may contain one or more aromatic ester repeating units generally represented by the following formula (I):

[0019]

[0020] in

[0021] Ring B is a substituted or unsubstituted 6-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted 6-membered aryl group fused to a substituted or unsubstituted 5-membered or 6-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted 6-membered aryl group linked to a substituted or unsubstituted 5-membered or 6-membered aryl group (e.g., 4,4-biphenylene); and

[0022] Y1 and Y2 are independently O, C(O), NH, C(O)HN or NHC(O).

[0023] Typically, at least one of Y1 and Y2 is C(O). Examples of such aromatic ester repeating units may include, for example, aromatic dicarboxyl repeating units (Y1 and Y2 in Formula I are C(O)), aromatic hydroxycarboxyl repeating units (Y1 in Formula I is O, and Y2 is C(O)), and various combinations thereof.

[0024] For example, aromatic hydroxycarboxylic repeating units derived from aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid; 4-hydroxy-4'-biphenylcarboxylic acid; 2-hydroxy-6-naphthoic acid; 2-hydroxy-5-naphthoic acid; 3-hydroxy-2-naphthoic acid; 2-hydroxy-3-naphthoic acid; 4'-hydroxyphenyl-4-benzoic acid; 3'-hydroxyphenyl-4-benzoic acid; 4'-hydroxyphenyl-3-benzoic acid, etc., as well as alkyl, alkoxy, aryl and halogen substitutes and combinations thereof can be used. Particularly suitable aromatic hydroxycarboxylic acids are 4-hydroxybenzoic acid (HBA) and 6-hydroxy-2-naphthoic acid (HNA). When used, repeating units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) typically account for about 20 mol.% to about 80 mol.%, in some embodiments about 25 mol.% to about 75 mol.%, and in some embodiments about 30 mol.% to 70 mol.%.

[0025] Aromatic dicarboxylic repeating units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl and halogen substitutes thereof and combinations thereof, can also be used. Particularly suitable aromatic dicarboxylic acids can include, for example, terephthalic acid (TA), isophthalic acid (IA) and 2,6-naphthalene dicarboxylic acid (NDA). When used, repeating units derived from aromatic dicarboxylic acids (e.g., IA, TA, and / or NDA) typically comprise from about 1 mol.% to about 50 mol.%, in some embodiments, from about 5 mol.% to about 40 mol.%, and in some embodiments, from about 10 mol.% to about 35% of the polymer.

[0026] Other repeating units can also be used in the polymer.For example, in certain embodiments, it is possible to use repeating units derived from aromatic diols, such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dimethylbiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis(4-hydroxyphenyl)ethane, etc. and alkyl, alkoxy, aryl and halogen substituents and combinations thereof. Particularly suitable aromatic diols can include, for example, hydroquinone (HQ) and 4,4'-biphenol (BP). When used, repeating units derived from aromatic diols (for example, HQ and / or BP) generally account for about 1% to about 40mol.%, about 2mol.% to about 35mol.% in some embodiments, and about 5mol.% to about 30% in some embodiments of the polymer. Repeating units, such as those derived from aromatic amides (e.g., acetaminophen (APAP)) and / or aromatic amines (e.g., 4-aminophenol (AP), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, etc.) may also be used. When used, repeating units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically comprise from about 0.1 mol.% to about 20 mol.%, in some embodiments from about 0.5 mol.% to about 15 mol.%, and in some embodiments from about 1 mol.% to about 10 mol.% of the polymer. It should also be understood that various other monomer repeating units may be incorporated into the polymer. For example, in certain embodiments, the polymer may contain one or more repeating units derived from non-aromatic monomers (e.g., aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, etc.). Of course, in other embodiments, the polymer can be "wholly aromatic," meaning that it lacks repeating units derived from non-aromatic (eg, aliphatic or cycloaliphatic) monomers.

[0027] Although not required, in the aspect that the liquid crystal polymer contains relatively high content of repeating units derived from naphthalene hydroxycarboxylic acid and naphthalene dicarboxylic acid (e.g., NDA, HNA or a combination thereof), the liquid crystal polymer can be a "high naphthalene" polymer. That is, the total amount of repeating units derived from naphthalene hydroxycarboxylic acid and / or naphthalene dicarboxylic acid (e.g., NDA, HNA or a combination of HNA and NDA) is generally about 10 mol.% or more of the polymer, in some embodiments about 12 mol.% or more, in some embodiments about 15 mol.% or more, in some embodiments about 15 mol.% to about 50 mol.%, and in some embodiments about 16 mol.% to about 30 mol.%. For example, in one embodiment, the repeating units derived from NDA are within the above range. The liquid crystal polymer may also include various other monomers. For example, the polymer may contain about 20 mol.% to about 60 mol.% of repeating units derived from HBA, in some embodiments, about 25 mol.% to about 55 mol.% of repeating units derived from HBA, in some embodiments, about 30 mol.% to about 50 mol.% of repeating units derived from HBA. The polymer may also contain about 1 mol.% to about 15 mol.% of aromatic dicarboxylic acids (e.g., IA and / or TA) and / or about 10 mol.% to about 35 mol.% of aromatic diols (e.g., BP and / or HQ). Of course, in other embodiments, the liquid crystal polymer may be a "low naphthalene" polymer, which contains relatively low levels of repeating units derived from naphthalene hydroxycarboxylic acids and naphthalene dicarboxylic acids (e.g., naphthalene-2,6-dicarboxylic acid (NDA), 6-hydroxy-2-naphthoic acid (HNA) or a combination thereof). That is, the total amount of repeating units derived from naphthalenehydroxycarboxylic acid and / or naphthalene dicarboxylic acid (e.g., NDA, HNA, or a combination of HNA and NDA) can be about 10 mol.% or less, in some embodiments about 8 mol.% or less, and in some embodiments, from about 1 mol.% to about 6 mol.% of the polymer.

[0028] It is generally desirable that a considerable portion of the polymer matrix is ​​formed by such high naphthalene polymers. For example, the high naphthalene polymers described herein generally account for 50 wt.% or more of the polymer matrix, in some embodiments about 65 wt.% or more, in some embodiments about 70 wt.% to 100 wt.%, in some embodiments about 80 wt.% to 100% (e.g., 100 wt.%). In some cases, blends of polymers may also be used. For example, low naphthalene liquid crystal polymers may account for about 1 wt.% to about 50 wt.% of the total amount of liquid crystal polymer in the composition, in some embodiments about 2 wt.% to about 40 wt.%, and in some embodiments about 5 wt.% to about 30 wt.%, while high naphthalene liquid crystal polymers may account for about 50 wt.% to about 99 wt.% of the total amount of liquid crystal polymer in the composition, in some embodiments about 60 wt.% to about 98 wt.%, and in some embodiments about 70 wt.% to about 95 wt.%.

[0029] B. Optional additives

[0030] In certain embodiments, the polymer composition may be formed entirely of a polymer matrix (i.e., 100 wt.%). Of course, in other embodiments, one or more additives may be distributed throughout the polymer matrix to help provide the desired properties. When used, such additives are typically from about 0.1 to about 300 parts by weight per 100 parts by weight of the polymer matrix, from about 0.5 to about 250 parts by weight in some embodiments, and from about 1 to about 200 parts by weight in some embodiments. The additive may, for example, account for from about 0.1 wt.% to about 80 wt.% of the polymer composition, from about 0.5 wt.% to about 70 wt.% in some embodiments, and from about 1 wt.% to about 60 wt.% in some embodiments.

[0031] For example, in a particular embodiment, the polymer composition may include a thermally conductive filler distributed within the polymer matrix. In order to help achieve the desired balance between thermal conductivity, high flowability and good mechanical properties, the relative amount of the thermally conductive filler is generally controlled to be about 10 to about 250 parts by weight per 100 parts by weight of the polymer matrix, about 40 to about 250 parts by weight in some embodiments, about 60 to about 200 parts by weight in some embodiments, and about 80 to about 190 parts by weight in some embodiments. The thermally conductive filler may, for example, account for about 20 wt.% to about 70 wt.% of the polymer composition, about 28 wt.% to about 62 wt.% in some embodiments, about 35 wt.% to about 65 wt.% in some embodiments, and about 40 wt.% to about 60 wt.% in some embodiments.

[0032] If desired, thermally conductive fillers may include materials with high intrinsic thermal conductivity. For example, polymer compositions may include materials with 50W / mK or higher, 100W / mK or higher, and 150W / mK or higher intrinsic thermal conductivity in some embodiments. Examples of such high intrinsic thermal conductive materials may include, for example, boron nitride, aluminum nitride, magnesium silicon nitride, graphite (e.g., expanded graphite), silicon carbide, carbon nanotubes, zinc oxide, magnesium oxide, beryllium oxide, zirconium oxide, yttrium oxide, aluminum powder, and copper powder. Although such materials may be used in certain embodiments, it has been found that high thermal conductivity can be achieved without the use of conventional materials with high intrinsic thermal conductivity. For example, polymer compositions may generally be free of fillers with intrinsic thermal conductivity. That is, such fillers may account for about 10wt.% or less of the polymer composition, about 5wt.% or less in some embodiments, and 0wt.% to about 2wt.% (e.g., 0wt.%) in some embodiments.

[0033] For example, in a particular embodiment, thermally conductive filler can include mineral particles. When used, such mineral particles are generally about 70 to about 250 weight parts per 100 weight parts of polymer matrix, about 75 to about 200 weight parts in some embodiments, and about 90 to about 190 weight parts in some embodiments. Mineral particles can for example account for about 30wt.% to about 70wt.% of polymer composition, about 35wt.% to about 65wt.% in some embodiments, and about 40wt.% to about 60wt.% in some embodiments. Mineral particles can be formed by natural and / or synthetic silicate minerals, such as talc, mica, halloysite, kaolinite, illite, montmorillonite, vermiculite, palygorskite, pyrophyllite, calcium silicate, aluminum silicate, wollastonite, etc. Talc is particularly suitable for polymer composition. The shape of the particle can be changed as required, such as granular, flaky, etc. The median particle size (D50) of the particles is generally from about 1 to about 25 microns, in some embodiments from about 2 to about 15 microns, and in some embodiments from about 4 to about 10 microns, as measured by sedimentation analysis (e.g., Sedigraph 5120). If desired, the particles may also have a high specific surface area, such as about 1 square meter per gram (m2 / g). 2 / g) to about 50m 2 / g, in some embodiments about 1.5m 2 / g to about 25m 2 / g, and in some embodiments about 2m 2 / g to about 15m 2 / g. The surface area can be determined by the physical gas adsorption (BET) method (nitrogen as adsorbed gas) according to DIN 66131:1993. The water content can also be relatively low, for example, about 5% or less, in some embodiments about 3% or less, and in some embodiments about 0.1 to about 1%, as determined according to ISO 787-2:1981 at a temperature of 105°C.

[0034] In addition to and / or in place of the mineral particles, the thermally conductive filler may also include mineral fibers (also referred to as "whiskers"). When used, such mineral fibers are typically present in an amount of about 10 to about 150 parts by weight, in some embodiments about 15 to about 100 parts by weight, and in some embodiments about 20 to about 80 parts by weight per 100 parts by weight of the polymer matrix. The mineral fibers may, for example, comprise about 10 wt.% to about 50 wt.%, in some embodiments about 15 wt.% to about 45 wt.%, and in some embodiments about 20 wt.% to about 40 wt.% of the polymer composition. Examples of such mineral fibers include those derived from silicates, such as monoisland silicates, archipelagic silicates, inosilicates (e.g., calcium inosilicates such as wollastonite; calcium magnesium inosilicates such as tremolite; calcium magnesium iron inosilicates such as actinolite; magnesium iron inosilicates such as anthophyllite; etc.), layered silicates (e.g., aluminum layered silicates such as palygorskite), reticular silicates, etc.; sulfates, such as calcium sulfate (e.g., dehydrated or anhydrite); mineral wool (e.g., rock wool or slag wool); etc. Particularly suitable are inosilicates, such as those available from Nyco Minerals under the trade name (For example 4W or 8) obtained wollastonite fibers. The median diameter of the mineral fiber may be from about 1 to about 35 microns, from about 2 to about 20 microns in some embodiments, from about 3 to about 15 microns in some embodiments, and from about 7 to about 12 microns in some embodiments. The mineral fiber may also have a narrow size distribution. That is, at least about 60 vol.% of the fiber, at least about 70 vol.% of the fiber in some embodiments, and at least about 80 vol.% of the fiber in some embodiments may have a size within the above range. In addition to having the above-mentioned size characteristics, the mineral fiber may also have a relatively high aspect ratio (average length divided by the median diameter) to help further improve the mechanical properties and surface quality of the resulting polymer composition. For example, the aspect ratio of the mineral fiber may be from about 2 to about 100, from about 2 to about 50 in some embodiments, from about 3 to about 20 in some embodiments, and from about 4 to about 15 in some embodiments. The volume average length of such mineral fibers may be, for example, from about 1 to about 200 microns, from about 2 to about 150 microns in some embodiments, from about 5 to about 100 microns in some embodiments, and from about 10 to about 50 microns in some embodiments.

[0035] The polymer composition can also include various other optional components to help improve its overall performance. For example, the polymer composition can include a metal hydroxide that can effectively "lose" hydroxide ions during processing with the polymer to initiate chain scission of the polymer, thereby reducing the molecular weight, thereby reducing the melt viscosity of the polymer under shear. When used, the metal hydroxide can be about 0.05 to about 10 parts by weight per 100 parts by weight of the polymer matrix, about 0.1 to about 5 parts by weight in some embodiments, and about 0.2 to about 3 parts by weight in some embodiments. For example, the metal hydroxide can account for about 0.01wt.% to about 5wt.% of the polymer composition, about 0.05wt.% to about 4wt.% in some embodiments, and about 0.1wt.% to about 2wt.% in some embodiments.

[0036] An example of a suitable metal hydroxide has the general formula M(OH) s , where s is the oxidation state (usually 1 to 3) and M is a metal such as a transition metal, an alkali metal, an alkaline earth metal or a main group metal. Examples of suitable metal hydroxides may include copper (II) hydroxide (Cu(OH)2), potassium hydroxide (KOH), sodium hydroxide (NaOH), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), aluminum hydroxide (Al(OH)2), s ) and the like. Also suitable are metal alkoxide compounds capable of forming a hydroxyl functional group in the presence of a solvent (e.g. water). Such compounds may have the general formula M(OR) s , where s is the oxidation state (usually 1 to 3), M is a metal, and R is an alkyl group. Examples of such metal alkoxides may include copper(II) ethoxide (Cu 2+ (CH3CH2O - )2), Potassium ethoxide (K + (CH3CH2O - ))、Sodium ethoxide (Na + (CH3CH2O - ))、Mg(III) 2+ (CH3CH2O - )2) Calcium ethoxide (Ca 2+ (CH3CH2O - )2) etc.; Aluminum ethoxide (Al 3+ (CH3CH2O - )3) etc. In certain embodiments, the metal hydroxide may be in the form of metal hydroxide particles. For example, the particles may include at least one metal hydroxide having the general formula Al(OH) a O bAluminum hydroxide, wherein 0≦a≦3 (e.g., 1) and b=(3-a) / 2. For example, in one specific embodiment, the particles exhibit a boehmite crystalline phase, and the aluminum hydroxide has the chemical formula AlO(OH) ("aluminum oxide hydroxide"). The metal hydroxide particles can be needle-shaped, elliptical, flaky, spherical, etc. In any case, the median particle size (D50) of the particles is typically from about 50 to about 800 nanometers, in some embodiments from about 150 to about 700 nanometers, and in some embodiments from about 250 to about 500 nanometers, as determined by non-invasive backscattering (NIBS) technology. If desired, the particles can also have a high specific surface area, for example, about 2 square meters per gram (m 2 / g) to about 100m 2 / g, in some embodiments about 5m 2 / g to about 50m 2 / g, and in some embodiments about 10m 2 / g to about 30m 2 / g. The surface area can be determined by the physical gas adsorption (BET) method (nitrogen as adsorbed gas) according to ISO 9277:2010. The water content can also be relatively low, for example, about 5% or less, in some embodiments about 3% or less, and in some embodiments about 0.1 to about 1%, as determined according to ISO 787-2:1981.

[0037] Other components that may also be included in the composition include, for example, reinforcing fibers (e.g., glass fibers), pigments (e.g., black pigments), antioxidants, stabilizers, crosslinking agents, lubricants, impact modifiers, flow promoters, and other materials added to enhance performance and processability.

[0038] II. Melt Processing

[0039] Liquid crystal polymer and various other optional additives (e.g., thermally conductive fillers, pigments, lubricants, etc.) can be combined in a manner as known in the art. For example, the material can be supplied to a melt processing device for dispersively mixing materials simultaneously or sequentially. Batch and / or continuous melt processing techniques can be used. For example, a mixer / kneader, Banbury mixer, Farrel continuous mixer, single screw extruder, twin screw extruder, roller mill, etc. can be used to blend and melt process materials. A particularly suitable melt processing device is a co-rotating twin screw extruder (e.g., Leistritz co-rotating fully meshing twin screw extruder). Such an extruder may include a feed port and a vent, and provide high-intensity distribution and dispersed mixing. For example, the components can be fed to the same or different feed ports of a twin screw extruder and the components can be melt blended to form a substantially uniform molten mixture. Melt blending can occur under high shear / pressure and heat to ensure sufficient dispersion. For example, melt processing may occur at a temperature of about 150° C. to about 450° C., and in some embodiments, at a temperature of about 250° C. to about 400° C. Likewise, the apparent shear rate during melt processing may be about 100 seconds. -1 to about 10,000 seconds -1 and in some embodiments within about 500 seconds. -1 to about 1,500 seconds -1 Of course, other variables, such as residence time during melt processing, which is inversely proportional to throughput rate, can also be controlled to achieve the desired uniformity.

[0040] If desired, one or more distribution and / or dispersive mixing elements may be used in the mixing section of the melt processing unit. Suitable distribution mixers may include, for example, Saxon, Dulmage, Cavity Transfer mixers, etc. Similarly, suitable dispersive mixers may include Blister rings, Leroy / Maddock, CRD mixers, etc. As is well known in the art, mixing can further improve aggressiveness by using pins that can produce folding and redirection of polymer melts in the barrel, such as those used for Buss Kneader extruders, cavity transfer mixers, and Vortex Intermeshing Pin mixers. The speed of the screw may also be controlled to improve the properties of the composition. For example, the screw speed may be about 400 rpm or less, in one embodiment, such as between about 200 rpm and about 350 rpm, or between about 225 rpm and about 325 rpm. In one embodiment, the compounding conditions may be balanced to provide a polymer composition that exhibits improved performance. For example, the compounding conditions may include a screw design to provide a mild, moderate, or aggressive screw condition. For example, a system may have a mildly aggressive screw design where the screw has a single melting section on the downstream half of the screw designed to achieve mild melting and distributive melt homogenization. A moderately aggressive screw design may have a stronger melting section upstream of the filler feed barrel that is more concentrated on stronger dispersing elements to achieve uniform melting. In addition, the moderately aggressive screw design may have another mild mixing section downstream to mix the filler. This section, while weaker, still increases the shear strength of the screw, making it stronger overall than the mildly aggressive design. A highly aggressive screw design may have the strongest shear strength of the three. The main melting section may consist of a long series of highly dispersive kneading blocks. The downstream mixing section may use a mix of distributing and dense dispersing elements to achieve uniform dispersion of all types of fillers. The shear strength of the highly aggressive screw design may be significantly higher than the other two designs. In one embodiment, the system may include a moderate to aggressive screw design with a relatively mild screw speed (eg, between about 200 rpm and about 300 rpm).

[0041] III. Stator core

[0042] The stator core generally includes a stator body from which extends a plurality of spaced-apart slot segments with intermediate slots defined therebetween. See, for example, Figure 1a, shows one embodiment of the stator body 2 of the stator core 1 in more detail. The stator body 2 generally has an annular shape formed by an outer peripheral wall, which defines an annular central hole for receiving a rotor. The stator body 2 includes a plurality of slot segments 3 (i.e., teeth) that are spaced apart from one another in the circumferential direction U and extend in an axial direction A along a central longitudinal axis M of the stator body 2, and are therefore perpendicular to the circumferential direction U. The radial direction R also extends perpendicularly away from the central longitudinal axis M, and is therefore orthogonal to the axial direction A and the circumferential direction U. The stator body 2 and / or the slot segments 3 may be formed of a conductive material, such as a variety of different metals, such as aluminum, stainless steel, magnesium, nickel, chromium, copper, titanium, and alloys thereof. As shown, the slot segments 3 extend between opposite ends of the body 2 and protrude radially toward the central hole. A slot 13 containing an intermediate space 4 is defined in the middle between segments 3 that are adjacent to one another in the circumferential direction. See FIG. Figure 1b , two slot segments 3 are shown which are arranged adjacent to each other in the circumferential direction U. At the end facing away from the stator body 2, each slot segment 3 includes extensions 12a, 12b protruding from the slot segment 3 along the circumferential direction U and against the circumferential direction U, so that the two extensions 12a, 12b of the two slot segments 3 adjacent to each other in the circumferential direction U and arranged opposite to each other in the circumferential direction U form the slot 13 on the radial inner side while partially limiting the intermediate space 4.

[0043] As described above, the polymer composition of the present invention is used for an insulating member disposed in one or more slots of a stator core. The insulating member may be relatively thin in nature, such as having a thickness of about 0.01 to about 4 mm, in some embodiments about 0.1 to about 2 mm, and in some embodiments about 0.2 to about 1 mm.

[0044] The ability to form such a thin insulating member for a stator can be achieved in a variety of ways. For example, in one embodiment, the polymer composition can be used to form a separate insulating member that is simply inserted into one or more separate slots. However, in another embodiment, the polymer composition can be simply molded onto the stator body (i.e., "overmolded") to form an insulating member that includes a portion that is located within one or more slots. Again referring to Figure 2a , 2b 2c, shows an integrally overmolded insulating component comprising a portion K1 located within the slot 13. If necessary, a first mask 6a (e.g., a sheet metal insert 17a) may first be introduced into the intermediate slots 4 between the slot segments 3 before overmolding. More specifically, the mask 6a may cover the surface portion 7 and may be introduced into the radially outer end 10a of the respective intermediate slot 13 and completely fill the respective radially outer end 10a.

[0045] Suitable molding techniques may include, for example, injection molding, low-pressure injection molding, extrusion compression molding, gas injection molding, foam injection molding, low-pressure gas injection molding, low-pressure foam injection molding, gas extrusion compression molding, foam extrusion compression molding, extrusion molding, foam extrusion molding, compression molding, foam compression molding, gas compression molding, etc. For example, an injection molding system may be used, which includes a mold into which the polymer composition may be injected. The time in the syringe may be controlled and optimized so that the polymer matrix is ​​not pre-cured. When the cycle time is reached and the barrel is full of discharge, the composition may be injected into the mold cavity using a piston. A compression molding system may also be used. As with injection molding, the polymer composition may be formed into the desired article in a mold. The composition may be placed in a compression mold using any known technique (e.g., by being picked up by an automatic robot arm). The temperature of the mold may be maintained at or above the curing temperature of the polymer composition and continued for a desired period of time to allow curing. Subsequently, the molded product may be cured by introducing it to a temperature below the melting temperature. The resulting product may be demoulded. The cycle time of each molding process may be adjusted to suit the polymer composition to achieve adequate bonding and improve the productivity of the entire process.

[0046] Regardless of the process used, one or more stator windings (e.g., copper wire) can be arranged on the slot segments to form the final stator, which is well known to those skilled in the art. For example, the windings can be arranged on portions of the slot segments and used to conduct current to provide relative movement of the rotor relative to the stator when used in an electric motor. In this manner, an insulating member or portion of an insulating member is disposed between the windings and the slot segments to electrically insulate the slot segments from the windings. In another embodiment, the windings can also be secured to the slot segments by an adhesive polymer composition, which can be the same or different from the polymer composition used to form the insulating member. For example, referring to Figure 3a , 3b and 3c, stator windings 5 ​​(eg, copper wire) are shown arranged on the slot segments 3 to form the stator.

[0047] As described above, the rotor (not shown) is configured to be disposed within the central bore of the stator core 1 and to rotate relative to the stator. In this manner, current passing through windings of the stator and / or rotor can drive the rotor to rotate relative to the stator. A shaft (not shown) may also be operably coupled to the rotor and configured to rotate with the rotor. The shaft is configured to facilitate conversion of mechanical energy (e.g., rotation) to electrical energy (e.g., current), or vice versa. The general relationship between the stator 100 and other components or aspects of a power system (e.g., a motor or generator) is described in detail in the accompanying drawings. Figure 4 Shown in. Figure 4A schematic diagram of a power system 200 according to various embodiments is provided. The power system 200 includes a rotor 210, a stator 220 (which may be substantially similar to the stator discussed herein in various aspects), a housing 230, and a shaft 240. The power system 200 may be configured as a generator or a motor. In various embodiments, the power system 200 may be configured for alternating current (AC) operation. In addition, in various embodiments, the power system 200 may be configured for direct current (DC) operation. Typically, the rotor 210 is configured to be disposed in a hole 222 or a central opening of the stator 220 and rotate relative to the stator 220. When the power system 200 operates as a motor, the current passing through the windings of the rotor 210 and / or the windings of the stator 220 causes the rotor 210 to rotate relative to the stator 220. When the power system 200 operates as a generator, the rotation of the rotor 210 relative to the stator 220 causes an outputtable current to be generated in the windings of the stator and / or the rotor 210. The current can be output by the generator for use by one or more external (e.g., external to the power system 200) devices and / or systems. The housing 230 in the illustrated embodiment provides support and mounting for the stator 220, helping to keep the stator 220 in a stationary position when the rotor 210 rotates. The housing 230 may also provide mounting features for mounting the rotor 210, such as one or more bearings. In addition, the housing 230 shown is configured to act as a heat sink or otherwise provide heat transfer from the stator 220. The shaft 240 is operably coupled to the rotor 210 and is configured to rotate with the rotor 210. The shaft 240 is configured to facilitate conversion of mechanical energy (e.g., rotation) into electrical energy (e.g., current), or vice versa. When the power system 200 operates as a generator, the shaft 240 is used to provide a rotational input to the power system 200 for generating current. When the power system 200 operates as a motor, the shaft 240 is used to output rotation for use by a system coupled to the power system 200.

[0048] The stator and power system can be used in a variety of product applications, but are particularly advantageous for electric motors used in electric vehicles, such as battery-powered electric vehicles, fuel cell-powered electric vehicles, plug-in hybrid electric vehicles (PHEV), mild hybrid electric vehicles (MHEV), full hybrid electric vehicles (FHEV), etc. For example, see Figure 5, shows an embodiment of an electric vehicle 12 including a powertrain 10. The powertrain 10 includes one or more motors 14 connected to a transmission 16, which in turn is mechanically connected to a drive shaft 12 and a drive wheel 22. Although by no means required, the transmission 16 in this particular embodiment is also connected to an engine 18, but the description here is equally applicable to pure electric vehicles. The motor 14 can be an electric motor including a stator / rotor system to provide propulsion and deceleration capabilities. The powertrain 110 also includes a propulsion source, such as a battery assembly 24, which stores and provides energy for use by the motor 14. The battery assembly 24 typically provides a high voltage current output (e.g., a DC voltage of about 400 volts to about 800 volts) from one or more battery cell arrays, which may include one or more battery cells.

[0049] The powertrain 10 may also include at least one power electronics module 26, which is connected to the battery assembly 24 (also commonly referred to as a battery pack) and may include a power converter (e.g., a converter, etc., and a combination thereof). The power electronics module 26 is generally electrically connected to the motor 14 and provides the ability to bidirectionally transmit electrical energy between the battery assembly 24 and the motor 14. For example, the battery assembly 24 may provide a DC voltage, while the motor 14 may require a three-phase AC voltage to operate. The power electronics module 26 may convert the DC voltage into a three-phase AC voltage according to the needs of the motor 14. In regenerative mode, the power electronics module 26 may convert the three-phase AC voltage from the motor 14 as a generator into the DC voltage required by the battery assembly 24. The battery assembly 24 may also provide energy for other vehicle electrical systems. For example, the powertrain may employ a DC / DC converter module 28, which converts the high-voltage DC output from the battery assembly 24 into a low-voltage DC supply compatible with other vehicle loads (e.g., a compressor and an electric heater). In a typical vehicle, the low-voltage system is electrically connected to an auxiliary battery (e.g., a 12V battery). There may also be a battery energy control module (BECM) 33 in communication with the battery assembly 24, which acts as a controller for the battery assembly 24 and may include an electronic monitoring system that manages the temperature and state of charge of each battery cell. The battery assembly 24 may also have a temperature sensor 31, such as a thermistor or other thermometer. The temperature sensor 31 may communicate with the BECM 33 to provide temperature data about the battery assembly 24. The temperature sensor 31 may also be located on or near a battery cell within the traction battery 24. It is also contemplated that more than one temperature sensor 31 may be used to monitor the temperature of a battery cell.

[0050] The battery assembly 24 can be charged by an external power source 36 (e.g., an electrical outlet). The external power source 36 can be electrically connected to an electric vehicle supply equipment (EVSE) that regulates and manages the transfer of electrical energy between the power source 36 and the vehicle 12. The EVSE 38 can have a charging connector 40 for plugging into a charging port 34 of the vehicle 12. The charging port 34 can be any type of port configured to transfer power from the EVSE 38 to the vehicle 12 and can be electrically connected to a charger or an onboard power conversion module 32. The power conversion module 32 can regulate the power supplied from the EVSE 38 to provide the appropriate voltage and current levels to the battery assembly 24. The power conversion module 32 can interact with the EVSE 38 to coordinate the delivery of power to the vehicle 12.

[0051] Test Method

[0052] Thermal conductivity: As known in the art, the thermal diffusivity of the sample in various directions (in-plane, across-plane, through-plane) can be preliminarily determined based on the laser flash method according to ASTM E 1461-13 (2022). The thermal conductivity (in-plane, across-plane, and through-plane) can then be calculated according to the following formula: Thermal conductivity (W / m*K) = Cp*ρ*α, where Cp is the specific heat capacity of the sample (J / kgK), ρ is the intrinsic density of the sample (kg / m) measured according to ISO 11831-1:2019 (Method A) 3 ), α is the measured thermal diffusivity (m 2 / s).

[0053] Melt viscosity: can be based on ISO 11443:2021, in 1000s -1 Melt viscosity (Pa-s) is measured using a Dynisco LCR7001 capillary rheometer at a shear rate of 1.5 %. The rheometer hole (die) may have a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an angle of incidence of 180°. The diameter of the barrel may be 9.55 mm + 0.005 mm, and the length of the rod may be 233.4 mm. The melt viscosity is typically measured at a temperature 15° C. above the melting temperature of the polymer and / or composition, for example, about 350° C.

[0054] Melting temperature: The melting temperature (Tm) can be determined by differential scanning calorimetry (DSC) as known in the art. The melting temperature is the differential scanning calorimetry (DSC) peak melting temperature as determined by ISO test number 11357-3:2018. Under the DSC procedure, as described in ISO standard 10350, the sample is heated and cooled at 20°C per minute using DSC measurements performed on a TA Q2000 instrument.

[0055] Tensile modulus, tensile stress at break, and tensile strain at break: Tensile properties can be tested according to ISO 527:2019 (technically equivalent to ASTM D638-14). Modulus and strength measurements can be performed on the same test strip sample with a length of 80 mm, a thickness of 10 mm, and a width of 4 mm. The test temperature can be 23°C, and the test speed for tensile strength and tensile strain at break can be 5 mm / min, and the test speed for tensile modulus can be 1 mm / min.

[0056] Flexural modulus and flexural stress: Flexural properties may be tested according to ISO 178:2019 (technically equivalent to ASTM D790-10). The test may be performed over a 64 mm support span. The test may be performed on the center portion of an uncut ISO 3167 multipurpose bar. The test temperature may be 23°C and the test speed may be 2 mm / min.

[0057] Charpy impact strength: Charpy properties can be tested according to ISO 179-1:2010 (technically equivalent to ASTM D256-10, method B). The test can be performed using a Type 1 specimen size (length 80 mm, width 10 mm and thickness 4 mm). The specimens can be cut from the center of the multi-purpose bar using a single tooth milling machine. The test temperature can be 23°C. For "notched" impact strength, the test can be performed using a Type A notch (base circle radius of 0.25 mm) and a Type 1 specimen size (length 80 mm, width 10 mm and thickness 4 mm).

[0058] Comparative Tracking Index (CTI): The Comparative Tracking Index (CTI) can be determined in accordance with International Standard IEC 60112-2003 to provide a quantitative indication of the performance of a composition as an electrical insulating material under conditions of moisture and / or contamination. In determining the CTI rating of a composition, two electrodes are placed on a formed test specimen. A voltage difference is then established between the electrodes when a 0.1% aqueous solution of ammonium chloride is dripped onto the test specimen. The maximum voltage at which five (5) specimens do not fail during a test period of 50 drops is determined. The test voltage range is 100 to 600V, in increments of 25V. The value of the voltage at which fifty (50) drops of electrolyte result in failure is the "Comparative Tracking Index". This value provides an indication of the relative tracking resistance of the material. According to UL746A, a nominal part thickness of 3mm is considered representative of performance at other thicknesses.

[0059] Examples 1 to 2

[0060] The following two (2) commercially available samples were compounded and injection molded for use in stator cores.

[0061]

[0062] LCP 1 is formed from 73% HBA and 27% HNA. LCP 2 is believed to be formed from 50% HBA, 25% BP and 25% TA. The samples were tested for mechanical properties, thermal properties and thermal conductivity as described herein. The results are as follows.

[0063] Example 1 Example 2 Tensile modulus (MPa) 9,887 14,000 Tensile strength(MPa) 50 143 Tensile elongation (%) 0.86 2.7 Flexural modulus (MPa) 13,500 13,000 Bending strength(MPa) 79 160 <![CDATA[Izod impact strength (without notch) (kJ / m 2 )]]> 7.0 29 <![CDATA[Izod impact strength (notched) (kJ / m 2 )]]> 3.6 10 DTUL(℃) 228 240 Tm(℃) 345-350 335 <![CDATA[1,000s -1 Lower melt viscosity (Pa-s)]]> 254(380℃) 42 TC, in-plane (W / mK) 9.4 2.5 TC, across the plane (W / mK) 9.0 1.0 TC, through plane (W / mK) 1.9 0.6 Dielectric strength (kV / mm) - 30 CTI(V) - 175

[0064] Example 3

[0065] The following samples were compounded and injection molded for use in stator cores.

[0066]

[0067] LCP 3 is formed from 43% HBA, 20% NDA, 9% TA and 28% HQ. The samples were tested for mechanical properties, thermal properties and thermal conductivity as described herein. The results are as follows.

[0068] Example 3 Tensile modulus (MPa) 10,000 Tensile strength(MPa) 82 Tensile elongation (%) 2.1 Flexural modulus (MPa) 10,000 Bending strength(MPa) 109 <![CDATA[Izod impact strength (unnotched) (kJ / m 2 )]]> 13 <![CDATA[Izod impact strength (notched) (kJ / m 2 )]]> - DTUL(℃) 261 <![CDATA[1,000s -1 Lower melt viscosity (MPa-s)]]> 43.6 Tm(℃) 315 TC, in-plane (W / mK) 4.8 TC, across the plane (W / mK) 3.4 TC, through plane (W / mK) 0.8 Dielectric strength (kV / mm) 41 CTI(V) 250

[0069] Without departing from the spirit and scope of the present invention, those of ordinary skill in the art may make these and other modifications and variations to the present invention. In addition, it should be understood that the aspects of each embodiment may be interchangeable as a whole or in part. In addition, those of ordinary skill in the art will appreciate that the foregoing description is exemplary only and is not intended to limit the present invention as further described in the appended claims.

Claims

1. A stator core, comprising: a stator body from which extend a plurality of spaced-apart slot segments, the slot segments defining intermediate slots therebetween; and An insulating member disposed in at least one of the intermediate grooves, wherein the insulating member comprises a polymer composition comprising a polymer matrix comprising a thermotropic liquid crystal polymer, further wherein the polymer composition exhibits a thermal conductivity of 1000 s at 1,000 s according to ISO 11443:2021. -1 The invention also provides a melt viscosity of about 300 Pa-s or less measured at a shear rate of about 1000 Pa and a temperature about 15°C higher than the melting temperature of the composition, and a deflection temperature under load of about 170°C or more measured under a load of 1.8 MPa according to ISO 75:2013. 2 . The stator core of claim 1 , wherein the stator body has an annular shape and defines a central hole for receiving a rotor. 3 . The stator core of claim 2 , wherein the slot segments are circumferentially spaced apart and protrude radially toward the center hole.

4. The stator core of claim 1, wherein the polymer composition exhibits a melting temperature of about 250°C to about 440°C.

5. The stator core of claim 1, wherein the thermotropic liquid crystal polymer comprises repeating units derived from one or more aromatic dicarboxylic acids, one or more aromatic hydroxycarboxylic acids, or a combination thereof. 6 . The stator core of claim 5 , wherein the aromatic hydroxycarboxylic acid comprises 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or a combination thereof. 7 . The stator core of claim 6 , wherein the aromatic dicarboxylic acid comprises terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, or a combination thereof.

8. The stator core of claim 5, wherein the liquid crystal polymer further comprises repeating units derived from one or more aromatic diols. 9 . The stator core of claim 8 , wherein the aromatic diol comprises hydroquinone, 4,4′-biphenol, or a combination thereof.

10. The stator core of claim 1, wherein the thermotropic liquid crystal polymer is fully aromatic. 11 . The stator core of claim 1 , wherein the thermotropic liquid crystal polymer includes a repeating unit derived from naphthalenehydroxycarboxylic acid and / or naphthalene dicarboxylic acid in an amount of about 10 mol. % or more.

12. The stator core of claim 1, wherein the polymer composition exhibits an in-plane thermal conductivity of about 2 W / mK or greater as measured according to ASTM E 1461-13 (2022).

13. The stator core of claim 1, wherein the polymer composition exhibits a trans-plane thermal conductivity of about 0.8 W / mK or greater as measured according to ASTM E 1461-13 (2022).

14. The stator core of claim 1, wherein the polymer composition exhibits an in-plane thermal conductivity of about 4 W / mK to about 8 W / mK measured according to ASTM E 1461-13 (2022).

15. The stator core of claim 1, wherein the polymer composition exhibits a dielectric strength of about 10 kV / mm or more as measured according to IEC 60234-1:2013.

16. The stator core of claim 1, wherein the polymer composition further comprises a thermally conductive filler.

17. The stator core of claim 16, wherein the thermally conductive filler comprises mineral particles.

18. The stator core of claim 17, wherein the mineral particles comprise talc.

19. The stator core of claim 17, wherein the mineral particles are present in an amount of about 70 to about 250 parts by weight per 100 parts by weight of the polymer matrix.

20. The stator core of claim 17, wherein the mineral particles have a median diameter of about 1 micron to about 25 microns and a specific surface area of ​​about 1 m2 as measured according to DIN 66131:1993. 2 / g to about 50m 2 / g, and / or a water content of about 5% or less as measured at a temperature of 105°C according to ISO 787-2:1981.

21. The stator core of claim 16, wherein the thermally conductive filler comprises mineral fibers.

22. The stator core of claim 21, wherein the mineral fibers comprise wollastonite.

23. The stator core of claim 21, wherein the mineral fibers are present in an amount of about 10 to about 150 parts by weight per 100 parts by weight of the polymer matrix.

24. The stator core of claim 1, wherein the polymer composition is free of fillers having an intrinsic thermal conductivity of 100 W / mK or greater.

25. The stator core of claim 1, wherein the polymer composition exhibits a comparative tracking index of about 170 volts or more measured at 3 millimeters thickness according to IEC 60112:2003.

26. The stator core of claim 1, wherein the insulating member is overmolded onto the stator body such that at least a portion of the insulating member is positioned within at least one of the intermediate slots.

27. A stator comprising a stator core according to any one of the preceding claims and at least one winding arranged on a slot segment of the stator core, wherein the insulating member is arranged between the winding and the slot segment.

28. A power system comprising the stator and rotor according to claim 27.

29. An electric vehicle comprising a powertrain comprising at least one electric propulsion source and a transmission connected to the propulsion source via at least one power electronics module, wherein: The electric vehicle includes the stator core according to any one of claims 1 to 26.